Estresse de enfermeiros em unidade de hemodinâmica - Linch, Graciele Fernanda da Costa (2009)
The following study is a transversal survey with a quantitative approach that aims to assess the relation between stress and symptoms presented by nurses working in Hemodynamics Wards (HW) in the state of Rio Grande do Sul. The data were collected through a survey for the identification of the nurses and the aspects related to their work (part I). Part II of the instrument composed by two Likert-like scales (Stressors Scale and Symptoms Scale presented by the nurses) and questions about the social habits. The piece of software Statistical Package for the Social Sciences (SPSS) has been used for data analysis, being the results considered statistically relevant if p < 0.05, with an interval of 95% of reliability. The population was constituted by 63 nurses, predominantly female (90.5%) and average age of 35.24(±8.21) years old. Most of the nurses were clinical ones (55.6%), worked in private institutions (77.4%), attended post-graduation studies (77.8%), and did not have another position (77.8%). They presented a formation time between one and ten years (61.9%) and 65.1% of the nurses worked for less than five years in HW. Most of the nurses got training to work with the HW (58.73%), did not make effort to go to work (85.71%), was satisfied with the work (85.71%), did not consider the day endless (84.13%), and were not willing to change profession (90.48%). Regarding stress, 52.4% of the nurses had an average between 1.11 and 1.97, classified as medium stress, and the areas with the highest averages were: critical situations (1.63 ± 0.29), followed by conflict function (1.58 ± 0.38), and overwork (1.56 ± 0.36). The variables that got higher score: overwork (2.34±0.84); having not very competent subordinated (2.31±1.16); intermediate conflicts between the areas, sectors, and wards (2.23±0.34); pressure concerning time (2.18±1.18); implement important decisions (2.17±0.98). Regarding symptoms, the domain skeletal-muscle alterations presented highest average (1.39±0.94), followed by changes in sleep and rest (1.01 ± 0.88). Among the variables stand out: lumbar pain (1.86±1.33); nape or cervical pain (1.78±1.30); excessive necessity to sleep (1.59±1.34); headache (1.56±1.16); sore muscle (1.48±1.12). In this study, there was a relevant positive high correlation between stress and symptoms presented by the nurses (r=0.629; p<0.001); it is concluded, thus, that stress is strictly related to the presented symptoms.